Proprietary Law Schools and the Marketization of Access to Justice - Tejani, Riaz (Social Science Research Network, 2016)
The rise of for-profit law schools in the United States highlights the interplay of political and moral economy in the reproduction of legal expertise. This article offers ethnographic evidence from one ABA-accredited for-profit law school pseudonymously labeled New Delta School of Law. The article posits New Delta as a case study in market fundamentalism of the kind first theorized by Hungarian economist Karl Polanyi. Polanyi defined global capital as a “double movement” between free marketeerism on the one hand and countervailing social protectionism on the other. Treating this as incomplete, social philosopher Nancy Fraser has since argued that the emancipatory new social movements form a third element in what should more properly be considered a “triple movement.” In this article, I argue that for-profit law schools such as New Delta support Fraser’s revision. Drawing in capital commitments from large institutional investors with promises of high returns on the basis of guaranteed federal student loan dollars, New Delta recruits disproportionately from minority and low-income communities while offering low chances of bar passage and legal employment. By marrying free marketeerism with the discourse of emancipation, the school has successfully evaded scrutiny.
Law; Legal Studies
Keywords: anthropology; economic; finance; law; legal education; markets; morals; neoliberalism; race; regulation; triple movement